iMuslims : Rewiring the House of Islam - Bunt, Gary R. (Book collections on Project MUSE., 2009)
Exploring the increasing impact of the Internet on Muslims around the world, this book sheds new light on the nature of contemporary Islamic discourse, identity, and community. The Internet has profoundly shaped how both Muslims and non-Muslims perceive Islam and how Islamic societies and networks are evolving and shifting in the twenty-first century, says Gary Bunt. While Islamic society has deep historical patterns of global exchange, the Internet has transformed how many Muslims practice the duties and rituals of Islam. A place of religious instruction may exist solely in the virtual world.